Rejoinder to Dominiak on bagels and donuts - Block, Walter E. (Wydawnictwo Uniwersytetu Wrocławskiego, 2022)
This is but the latest in a series of debates I have been having with my friend and colleague, Łukasz Dominiak. Included are the following texts: Block (2021), Dominiak (2017; 2019; 2021). We have been agreeing and disagreeing with each other concerning the implications of the bagel and donut theory for a while. The present paper continues this tradition: both agreeing and disagreeing with each other in regards to libertarian theory and trespass on private property.
Keywords: the Blockian Proviso; private property rights; easements; compensation